Clinical outreach refresher trainings in crisis settings (S-CORT): clinical management of sexual violence survivors and manual vacuum aspiration in Burkina Faso, Nepal, and South Sudan. Issue 51 (30th November 2017) - Tran, Nguyen Toan; Harker, Kristen; Yameogo, Wambi Maurice E.; Kouanda, Seni; Millogo, Tieba; Menna, Emebet Dlasso; Lohani, Jeevan Raj; Maharjan, Om; Beda, Sake Jemelia; Odinga, Elizabeth Akinyi; Ouattara, Adama; Ouedraogo, Charlemagne; et al.
Abstract: During the early humanitarian response to a crisis, there is limited time to train health providers in the life-saving clinical services of the Minimum Initial Services Package (MISP) for Reproductive Health. The Training Partnership Initiative of the Inter-agency Working Group on Reproductive Health in Crises developed the S-CORT model (S exual and reproductive healthC linicalO utreachR efresherT raining) for service providers operating in acute humanitarian settings and needing to rapidly refresh their knowledge and skills. Through qualitative research, this study aimed to determine the operational enablers and barriers related to the implementation of two S-CORT modules: clinical management of sexual violence survivors (CMoSVS) and manual vacuum aspiration (MVA). Across three participating countries (Burkina Faso, Nepal, and South Sudan), 135 health staff attended the CMoSVS refresher training and 94 the MVA refresher training. Results from the focus group discussions and in-depth interviews suggest that the S-CORT approach is respectful of human rights and quality of care principles. Furthermore, it is potentially effective in enhancing the knowledge and skills of existing trained service providers, strengthening their capacity, and changing their attitudes towards abortion-related services, for example. The S-CORT is a promising model for implementation in the acute phase of an emergency upon stabilisation of the security situation. The model can also be integrated into broader post-crisis capacity development efforts. Future operational research should emphasise not only an assessment of new modules' contents, but whether implementing this refresher training model in remote outreach settings is feasible, effective, and efficient.